PERAN SERTA KELOMPOK TANI DALAM PELESTARIAN HUTAN MANGROVE DI KAWASAN KABONGA BESAR KECAMATAN BANAWA KABUPATEN DONGGALA - Wiakanti, Liska; Rahman, Imran; Toknok, Bau (Universitas Tadulako, 2016)
Mangrove forest is a group of plant species that grow along tropical coast line to sub tropical coast line that has special function in the environment that contain salt and a land of coast. Mangrove forest is primary ecosystem in supporting an important life in coastal and ocean area. Other of its ecological fucntion as nutrient supllier for water biota, other biota, beach abrasion preventative, lunge of typhoon and tsunami, waste absorber, sea water interusion preventative. Mangrove ecosistem has function of supporting of higher human life than other ecosistem because of the very high primary productivity. Central Sulawesi has mangrove forests that spread in some areas one of them is in Kabonga Besar village. The research was conducted from April 2015 up to May 2015 in Kabonga Besar village Banawa subdistrict Donggala district, that aimed to find out how the active role of farmers community in preserving the mangrove forest in Kabonga Besar village Banawa subdistrict Donggala district. The data gathering was done by observing and interviewing with questionnaire. The data analysis used quantitative descriptive and used double Regresi linear analysis. The result of the research showed that the role form of farmers community in Kabonga Besar village Banawa subdistrict Donggala district that not throwing waste to the mangrove ecosystem, and not parking boat on mangrove ecosystem. The factor of work program was the factor that influenced mostly in the efforts of the mangrove preservation by the farmer community in Kabonga Besar village Banawa subdistrict Donggala district..Keywords: Farmers community, Mangrove forest, Kabonga Besar area.